2014
DOI: 10.1002/eat.22287
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic process in psychological treatments for eating disorders: A systematic review

Abstract: As most studies assessed only a limited number of process aspects, the ability to draw conclusions about their overall impact regarding outcome is rather limited. Therefore, future process-outcome research is needed beyond investigations of treatment efficacy for eating disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 172 publications
(349 reference statements)
1
49
0
2
Order By: Relevance
“…therapeutic alliance, group cohesion or experience of universality among group members facilitating treatment effects. For EDs the impact of such mechanisms in CBT treatment is less understood [18, 3133, 35, 36] in particular with respect to BN and BED [34], and for obvious reasons completely unknown with respect to the novel physical exercise and dietary treatment program. The exploring of the impact of such mechanisms imply a search for the mediation effects and when such effects occur during the course of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…therapeutic alliance, group cohesion or experience of universality among group members facilitating treatment effects. For EDs the impact of such mechanisms in CBT treatment is less understood [18, 3133, 35, 36] in particular with respect to BN and BED [34], and for obvious reasons completely unknown with respect to the novel physical exercise and dietary treatment program. The exploring of the impact of such mechanisms imply a search for the mediation effects and when such effects occur during the course of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary therapy (DT) and counseling alone to correct the chaotic eating pattern has unclear empirical support [5, 30], but one review indicate some support to a possible additive effects of DT with CBT [31]. The present trial is the first one to examine the additive effects of DT and PE (PED-t) compared to CBT alone, and using a group therapy format.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important limitation of this study is that we did not inquire about clinician factors such as therapeutic alliance with the parents, which may facilitate or impede family empowerment. This limitation has been identified in a recent review article that demonstrated that therapist variables are minimally examined in process‐oriented research in EDs (Brauhardt et al ., ). It was also beyond the scope of this study to assess whether the participants were adhering to the manualized version of FBT.…”
Section: Discussionmentioning
confidence: 99%
“…In EDs, RR is usually defined as a considerable reduction (e.g., 50–80%) in binge eating or purging or a percentage of weight regain in the context of weight restoration by the fourth week of treatment. These improvements have consistently predicted better outcomes in ED treatment . However, cut‐offs used to identify RR do not take into account the principle of equifinality, which suggests that an individual may meet the same criterion (i.e., for RR) via different pathways.…”
Section: What Is a Sudden Gain And How Does It Differ From Rapid Respmentioning
confidence: 99%